Development of Cyber Weapons to Improve Indonesia's Cyber Security - Achmad Wardana; Gunaryo Gunaryo; Y.H. Yogaswara (Syntax Corporation Indonesia, 2022)
It is indisputable that technical advancements have an impact on a country's military capability and security. This is inextricably linked to the deployment of numerous technologies and new discoveries aimed at boosting the military's defense system. As a result of this predicament, all governments are attempting to modernize their defense systems in order to deal with dangers posed by technological advancements. This is both a challenge and an opportunity for Indonesia's existing defense system. The goal of this study is to look into the development of cyber weapons and how they may help Indonesia improve its cyber security. The purpose of this study is to utilize a descriptive qualitative technique to investigate or explain the concerns surrounding the importance of cyber weapons in strengthening cyber security in Indonesia. The conclusions of this study show that as the number of Internet users grows, so does the global trend of cyber attacks. It's difficult to compare precision cyberweapons systems to existing kinetic weapons because of their new nature. Additionally, the development and use of cyber weapons can yield economic rewards. Human resources, as well as support and cooperation from Indonesian cyber defense groups with professionals in the field of hacking, are all crucial variables to consider while designing cyber weapons.